Asymptotic Behavior of the Solution to a Model System in Linearly Viscous Materials (Journal of Partial Differential Equations, 1999)
In this paper, we investigate the asymptotic behavior of solution to a model system in linearly viscous materials with temperature-dependent viscosity.
Keywords: Asymptotic behavior; smooth solution; model system; temperature-dependent viscosity; linearly viscous materials